Potential inhibitors of α-glucosidase and α-amylase enzymes from local fruit waste by solid state fermentation - Ahmad Barkat, Anumsima; Jamal, Parveen; Noor Batcha, Ibrahim Ali; Zainudin, Zaki; Suhaida Azmi, Azlin; Arbain, Dachyar; Mohamed Idris, Zulkarnain (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
One therapeutic approach for treating diabetes is to decrease the post-prandial hyperglycaemia. This is done by retarding the absorption of glucose through the inhibition of the carbohydrate hydrolyzing enzymes, α- amylase and α-glucosidase, in the digestive tract. Inhibition of both enzymes will help to reduce glucose level in the blood of diabetic patient. This study was aimed to investigate the production of α-glucosidase and α- amylase inhibitors from local fruit wastes (honeydew skin, banana peel, and pineapple skin) using solid state fermentation. Each of the fruit waste was fermented with three different types of white rot fungus (Phenarochaete chrysosporium (P.chrysosporium), Panus tigrinus MQR609 (M6) and RO2) for 7 days. Sampling was done starting from day 4 to day 7 to determine enzyme inhibition activity. The samples were extracted using water prior to enzyme analysis. Most of the fruit samples showed varying degrees of percentage inhibition activity depending on the sampling time. Extract of fermented banana peels with RO2 on day 4 showed higher potential of α-glucosidase inhibition (56.57±0.32%). Followed with honeydew extract fermented with the same fungus on the same day showed 39.68±0.05%. Extracts of each fruit wastes sample fermented with P.chrysosporium showed least potential of α-glucosidase inhibition (below 15%). While for α- amylase inhibition activity the extract from fermented honeydew skins with P.chrysosporium on day 7 showed the highest potential inhibition activity 98.29±0.63%. The least potential inhibition activity occurred in extract from honeydew skins fermented with M6 on day 5 showed 43.37±0.54%. All the positive result showed that fruit waste can be alternatives sources for antidiabetic agent especially for α-amylase and α- glucosidase inhibitors.